PELAKSANAAN PERATURAN DAERAH NO 19 TAHUN 2015 DI KABUPATEN MAJENE PERSPEKTIF HUKUM ISLAM - Mangkualam, Asnawi Anwar; Marilang, Marilang (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2020)
The main problem of this article is how to implement the Regional Regulation of Majene Regency Number 19 of 2015 in the Permit for the Establishment and Arrangement of Self-Service Layout in Majene Regency from an Islamic Law Perspective. This type of research is classified as field research with a syar'i normative theology approach and an empirical juridical normative approach. The results of this study indicate that the application of the Regional Regulation of Majene Regency number 19 of 2015 in the application of the permit to establish supermarkets in Majene Regency shows that the application of the permit to establish supermarkets in Majene has been implemented, but the application for the establishment permit has not been maximized because there are still violations and points that have not been carried out in accordance with perda In view of Islamic law, the protection of the empowerment of small businesses and traditional markets is an activity that updates the development of human life so that they can benefit with ulil amri from government decisions, in accordance with Maqāṣid al-Syari'ah.